Urban Infrastructuring Reconfigurations, Transformations and Sustainability in the Global South - Iossifova, Deljana; Gasparatos, Alexandros; Zavos, Stylianos; Gamal, Yahya; Long, Yin. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book is about urban infrastructuring as the processes linking infrastructural configurations and their components with other social, ecological, political, or otherwise defined systems as part of urbanisation and globalisation in the Global South. It suggests that infrastructuring is essential to urbanisation and that it is entangled with socio-spatio-ecological transformations that often have negative outcomes over time. Furthermore, it argues that infrastructuring requires an ethical positioning in research and practice in order to enhance infrastructural sustainability in the face of intersecting environmental, social and economic crises. "Urban Infrastructuring" is developed in three parts. First, it identifies infrastructural entanglements across various urban and urbanising settings in the Global South. Second, it highlights some of the damaging processes and outcomes of urban infrastructuring and argues that the absence, presence and transformation of infrastructure in the Global South (re-)produces socioecological injustice in the short- and long term. Third, the book argues for a shift of infrastructuring agendas towards more just and sustainable interventions. It suggests that an ethico-politics of care should be embedded in systems approaches to infrastructuring in both research and practice. The edited volume contains contributions from authors with backgrounds in a variety of academic disciplines from the natural and social sciences, engineering and the humanities. It provides valuable insights for anyone concerned with the study, design, planning, implementation and maintenance of urban infrastructures to enhance human well-being and sustainability. It will be of interest to researchers and urban decision-makers alike.
Chapter 1. Introduction: trajectories of infrastructural entanglement in cities of the Global South -- Chapter 2. Fragmented Infrastructure Systems in Ulaanbaatar, Mongolia: Assessment from an Environmental Resource Nexus and Public Health Perspective -- Chapter 3. What Lies Behind the Acute Crises: The Social and Infrasystems Links with Disasters in Brazil -- Chapter 4. Teaching, Therapy and Tourism: Infrastructural Transformations in Contemporary Chinese Theatre -- Chapter 5. The Infrastructures of Land: Heterogeneous Land Administration in Urban Ghana -- Chapter 6. Land Market Procedures and Market Preferences in Land Use Change: The Case of Greater Cairo -- Chapter 7. Sustainability of Municipal Solid Waste Management in Bolivian cities: Challenges, opportunities, and responses -- Chapter 8. Building Inequality: Infrastructure and Intra-Urban Inequality in the Capitalist City -- Chapter 9. Creating Age-Friendly Informal Settlements? Challenges to Enabling Health and Well-being for Older People in Informal Urban Harare -- Chapter 10. Transitioning Infrastructures and Socio-cultural Practices at the Idol-making Cluster of Kolkata' Kumartuli -- Chapter 11. Construction site assemblages: relationships of synergy and exploitation in the (re)configuration of Lekki, Nigeria -- Chapter 12. One Size Does Not Fit All: Sanitation Solutions in Shanghai's Older and Under-serviced Inner-city Neighbourhoods -- Chapter 13. Manufacturing open defecation free cities: punishing people and collapsing toilets, unpacking paradoxes of Mumbai's sanitation landscape -- Chapter 14. Modelling Chinese Urban Residential Stock Turnover Uncertainties Using System Dynamics and Bayesian Statistical Inference -- Chapter 15. A Strategic Planning Problem: The Unpredictability of Urban Transformation Based on the Changing Temporal Order of Planned Projects -- Chapter 16. The Importance of Social Infrastructure in Supporting Physical Infrastructure and Enabling the Development of Sustainable Cities -- Chapter 17. Architecture, Sanitation and COVID-19: design interventions in resource-limited settings (Accra, Ghana) -- Chapter 18. Speculative Futures of Global South Infrastructures -- Chapter 19. Infrastructuring with Care in Cities of the Global South.
Keywords: Sociology, Urban; Dynamics; Nonlinear theories; Geography; Public health; Civil engineering; Biotechnology; Urban Sociology; Applied Dynamical Systems; Regional Geography; Public Health; Civil Engineering; Biotechnology